Pengembangan Media Pembelajaran INKA (Ide Nasihat Kreativitas Anekdot) pada Materi Teks Anekdot Siswa Kelas X SMA Negeri 2 Tanjungpinang Tahun Pelajaran 2023/2024: Pengembangan Media Pembelajaran INKA (Ide Nasihat Kreativitas Anekdot) pada Materi Teks Anekdot Siswa Kelas X SMA Negeri 2 Tanjungpinang Tahun Pelajaran 2023/2024 - Inka Puspita Ningrum; Isnaini Leo Shanty; Siti Habiba (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This research has the aim of developing learning media ideas anecdote creativity advice (INKA) on anecdote text material for grade X high school students Negeri 2 Tanjungpinang in the 2023/2024 school year. This research uses the 4D model until the development stage. The product developed is in the form of visual learning media with impraboard as the base material. Media his learning media has been assessed by two experts, namely media experts and material experts. Trial test this media trial was conducted on two groups of students, namely 6 students for small groups and 40 students for large groups. Data collection techniques in this study, namely interviews, media validation questionnaires by media experts and material experts, as well as questionnaires of media practicality by students. Data analysis techniques in this study were carried out with two techniques, namely descriptive qualitative and descriptive quantitative. Media expert validation got an average of 95% with the qualification of "very valid" and material validation got an average of 100% with the qualification "very valid". In addition, this research was tested on SMA Negeri 2 Tanjungpinang students with a percentage of 88% with a qualification of "very practical" in small groups and percentage of 86% with the qualification "very practical" in the large group. Research This research can be used as a reference for further research to determine the level of effectiveness of the idea of anecdotal creativity advice (INKA) and can also be used as a reference in developing other creative visual media.